Global trends of Pauwels type III femoral neck fractures: bibliometric analysis and visualized study - Wang, Mengyu; Zhang, Ze; Sun, Fengpo; Zhu, Yi; Han, Ruining; Pei, Zijie; He, Zhaoshuo; Liu, Junzhi; Wen, Liangyuan (Frontiers in Surgery, 2024)
BackgroundPauwels type III femoral neck fractures, as a serious type of femoral neck fractures, have brought about a heavy economic burden on families and society for the high disability rate. Through bibliometric research and visualized analysis, this study aimed at elucidating the global research status of Pauwels type III femoral neck fractures to date, and predicting the future research trends in this field.MethodsPublications and associated information on Pauwels type III femoral neck fractures to date were retrieved from Web of Science Core Collection, and by VoSviewer and R package “bibliometrix”, bibliometric analysis and visual presentation was conducted.ResultsBy retrieval, a total of 98 studies were refinedly extracted, and the volume of publications in this field increased year-over-year. China ranked first in terms of total publication volume and H-Index, with its total citation records second only to the United States. The country with the highest average citation frequency was Switzerland. SHANGHAI JIAO TONG UNIVERSITY was the most productive research institution. Among the authors in this field, Li, Jiantao had published the most researches. INJURY INTERNATIONAL JOURNAL OF THE CARE OF THE INJURED and JOURNAL OF ORTHOPAEDIC TRAUMA were the two magazines with the highest publication volume, total citation records, and H-index. According to keywords co-occurrence analysis, the research content in the past 24 years is mainly divided into four different dimensions. Finite element analysis, femoral neck system, medial buttress plate, cannulated screws, hip screw, open reduction, complications are hot topics for future research.ConclusionsAccording to the global trends analysis of publications production, Pauwels type III femoral neck fractures are receiving increasing attention and input from scholars. China has made the greatest scientific research contribution among countries, but its academic quality should be improved further. The modified therapeutic methods designed for addressing the complications of traditional internal fixation for Pauwels III femoral neck fractures will be the future research hotspot.